TIGO LAREH: SISTEM KEKUASAAN DAN KONSEP ESTETIKA MUSIKAL TIGA GENRE MUSIK DI LUHAK NAN TIGO MINANGKABAU - Andar Indra Sastra; Wilma Sriwulan; Yon Hendri (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
The purpose of this study was to uncover and discover the influence of the power of tigolareh (three laras) in shaping the aesthetic concepts and theories of three traditional music genres in Luhak Nan TigoMinangkabau. TigoLareh’s system of power emerged as a political-legal reality that comes from two legendary Minangkabau figures, namely Dt. Katumangguangan and Dt. Parpatiah Nan Sabatang. Told in a story of traditional historiog-raphy, the two involved in ideological conflict in establishing a system of ‘governance’ (power) in Minangkabau called LarehKotopiliang and LarehBodicaniago. LarehKotopiliang, in his system of government, is character-ized by royal autocracy and LarehBodicaniago is more democratic in nature. The ideological conflict between the two figures gave rise to the third figure, namely RajoBabandiang, who held the title of Dt. Nan SakelapDunia, who then give birth to the concept of Lareh Nan Buntathat is a synthesis of both systems. The musical reality of bronze talempong music - is part of the (power) cultural system of LarehKotopiliang, and can be divided into two genres, namely: (1) the talempongbararak genre (procession), and; (2) talempong genre duduak (sitting). Talempongbararak appears in the form of “arakan” music and talempongduduak is played on the Java rea: rancakan and usually use gongs. LarehBodicaniago’s musical concept is populist and it is oriented to the power of vocal music (dendang) which in its presentation it is tied to the concept of bagurau (joking) which is accompanied by a musical instrument saluang (a type of wind instrument typical of Minangkabau). Meanwhile, the musical concept of Lareh Nan Bunta reflects the synthesis of both bronze musical concepts and vocal music (dendang). The musical concept of bronze music gave birth to the concept of talempongbasaua which was presented in the form of a hocketting technique. Tigolareh as a symbol of power synchronized with the reality of musical culture in its society.